If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(5x + 2) = -14 Reorder the terms: x + -1(2 + 5x) = -14 x + (2 * -1 + 5x * -1) = -14 x + (-2 + -5x) = -14 Reorder the terms: -2 + x + -5x = -14 Combine like terms: x + -5x = -4x -2 + -4x = -14 Solving -2 + -4x = -14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -4x = -14 + 2 Combine like terms: -2 + 2 = 0 0 + -4x = -14 + 2 -4x = -14 + 2 Combine like terms: -14 + 2 = -12 -4x = -12 Divide each side by '-4'. x = 3 Simplifying x = 3
| 21p^2+20p-25=0 | | 7m+10m=102 | | -8(2n+8)=-40+8n | | -2x-4x=-136 | | f^3-9f=0 | | (3x+5)(2x-3)=(x-1)(6x+5) | | 2(1-6x)+8=-38-4x | | -5o-9=4n+2 | | 5k-(2-1)k=13-7 | | -11.7x=46.8 | | 9a^2+21ac+10c^2= | | 10x-20x=2x-6 | | 5s-9=4s+2 | | x+4(x)=48 | | 8x-8(1+6x)= | | 6+2t-2=8t+20-4t | | -3(2b+1)+(7b-9)=0 | | 5x-y=180 | | 4(-8+3x)=4x+24 | | 3.9q-5.5-5.7q=-2.8q-3.4 | | 6n+13n=95 | | 19-ln(4-x)=0 | | 3b^2-17b-6= | | 3(8p-7)=-21+2p | | x+43=85 | | 7x-4(-3x-4)=-155 | | z+15-9=0 | | -2.5c+6.7=-13 | | 6x*6=8x-14 | | 6s^2-11s+3= | | 1+y=2.4 | | 42p+14=7(6p+2) |